LITERATURE REVIEW HUBUNGAN STRES DENGAN KEJADIAN HIPERTENSI - Muhammad Ridho; Agnes Frethernety; Tri Widodo (Jurnal Kedokteran Universitas Palangka Raya, 2021)
Hipertension is one of the major cause of mortality in the world as a non-communicable disease. During hypertension heart is under very high pressure of workload, one of the causative factor of hypertension is stress. Elevation of blood pressure appear more significant in individual with high susceptibility to stress. The purpose of this review is to assess the association between stress level and hypertension. The collection of literature in this review is done through Google Scholar, with association, strees, and hypertension as the keywords. Literatures were screened using inclusion and exclusion criteria and 19 were included in this review. As the result, 4 literature (21,05%) shows that no signicant association between stress and hypertension. Meanwhile, 15 literature (78,95%) shows there is significant association between the two variables. This review indicates that mild, moderate, and severe level of stress contributes to various stages of hypertension. The conclusion of this review is stating that the higher the stress level, the higher the incidence of hypertension in individuals. Meanwhile, the lower the stress level, the lower the incidence of hypertension. More of that, some prevention measures need to be taken to avoid progression of stress and avoid elevation of hypertension to higher stages and to prevent further complication such as stroke, heart failure, and other dangerous complications.